Identity, development, and the politics of the past: an ethnography of continuity and change in a coastal Ecuadorian community - Bauer, Daniel, author; University Press of Colorado, publisher (Colorado State University. Libraries, 2018)
Combining personal narrative and ethnography, Bauer examines cultural change in a rural Ecuadorian village where community has worked to stake claim to an Indigenous identity in face of economic, social, and political integration. Bauer shows how villagers reconstructed their identity and ethnicity in a complex social matrix.--Provided by publisher.
1. Introduction: Into the Field -- 2. Community, Economy, and Identity -- 3. Encountering the Past: Archaeology, Materiality, and the Foundations of Identity -- 4. Indigeneity in Uncommon Places: Representation, Plurinationalism, and the Multiple Meanings of Indigeneity -- 5. Development and Identity -- 6. Closing: Reflections on Change and Continuity.
Keywords: Ecuadorians -- Ethnic identity; Salango (Ecuador) -- Social conditions; Salango (Ecuador) -- Economic conditions; Ecuador -- Ethnic relations; Ecuador -- Politics and government